What makes a good nursing education: Meeting the needs of students and society in a free-market education system – cluster analysis of United Kingdom universities - Purssell, Edward; Sagoo, Rohit (Nurse education in practice, 2025)
Examine quality of education through classification of universities providing undergraduate pre-registration nursing courses in the United Kingdom using data from university league tables. Educational quality for nursing courses can be defined in many ways. University league tables are often used, but it can be difficult to interpret these because of the diversity of measures. These include educational input and output measures, but are not patient focussed. Cluster analysis of league table data. Data were from the Complete University and Guardian University League Tables. Cluster analysis was undertaken using euclidean distance and average linkage. Data were scaled by turning each value into a percentage of the maximum possible score. Careers and graduate prospects for nurses are high. Satisfaction with teaching and feedback are closely related and while these broadly cluster with research quality but there was a weak relationship between research quality and overall student satisfaction (correlation −0.008, SE 0.049, p = 0.869, adjusted R2 = −0.014). There was no clear pattern and few universities excelled in all areas. Traditional methods of ranking universities does not fit nursing well, where employment is higher and research quality lower than other subjects. There was no clear pattern in university results. Countries considering a free-market approach to nurse education should consider how they will meet the needs of students and health and social care services, while promoting research. The quality of nursing education should include broader measures of societal value and address the theory-practice gap.